(untitled) (AmS-Skrifter, 2026)
This paper presents a comparison of Scandinavian spear heads of the Vennolum type through the use of Principal Component Analysis in order to examine the sustainability of an alleged supra-regionality of weapon typology in early 3rd century Scandinavia. It shows that such a supra-regional similarity is exaggerated. There is considerable variation within type Vennolum spear heads and some of these variations have clear regional tendencies.